ANDRAGOGY AND PEDAGOGY: LEARNING METHOD ORIENTATIONS FOR EFL ADULT LEARNERS - Rismiyanto Rismiyanto (Universitas Negeri Padang, 2016)
Teaching English as foreign language in universities today is demanded to have a paradigm shift, from past passive learning to active learning, to find better ways of engaging students in the learning process. However, many teachers feel a need for help in imagining what to do, in or out of class that will constitute a meaningful set learning experience. Students in universities belong to the category of adult learners. They need to be treated more gently and given more chance to learn independently. An appropriate delivery method offered to support the adult learners to learn is andragogy, instead of using the other one delivery method to support the young learners to learn, pedagogy.This study is to compare the andragogically and pedagogically orientated learning methods for English as a foreign language adults learners. The EducationalOrientationQuestionnaire (Christian, 1983) is used. Sixty adults at Speaking for Instructional Purposes classes in English Education Department Muria Kudus University are included in the study. The results revealthatthesubjects are more to have orientation of andragogy than that of pedagogy. However, the wide range of scores suggested that they were not rigid in their orientations and tended to hold pedagogical tendency towards learning too.